Ethnocultural Youth Education in Musical Ensembles of Higher Schools - Jucevičiūtė-Bartkevičienė, Vaiva; Palubinskienė, Vida; Tavoras, Vilius (Acta Paedagogica Vilnensia, 2017)
This research analyzes the approach of Lithuanian, Latvian and Polish school youths to music performance in an ethnocultural ensemble as a means for the development of ethnic and cultural identity (national identity). The motives for choosing the nonformal music activities in an ethnocultural ensemble, the importance of ethnocultural education in young people’s lives and the problems of ethnocultural music education are analyzed. The higher schools experiences of ethnocultural non-formal music education of neighboring countries (Latvia and Poland), associated with Lithuania by cultural and historical links, are disclosed. Our research poses several questions. What is the concept of ethnic culture among young people in higher education schools in Lithuania, Latvia and Poland? What motives determine young people’s decisions to participate in ethnocultural musical ensembles of nonformal education? What value do they see in the participation in ethnocultural musical ensembles? Methods of collecting the research data included a qualitative study, which was conducted in Lithuania, Latvia and Poland in 2015-2016. A questionnaire survey using open-ended questions that were presented in the Lithuanian, English and Polish languages was employed to gather information. Participants of the study were students of higher education institutions, they provided written opinions. A qualitative content analysis was used in the processing of data.
Keywords: ethnocultural education; music education; non-formal education; adults’ learning